Pedagogical -Psychological Preparation Of Future History Teachers In Practical Activity - Rahimov Bobir Bakhodirovich (Open Academia, 2024)
in this article, the conditions for the development of the personal and pedagogical qualities of the future history teacher depends on the system, but also on various aspects of practical application of knowledge, skills and abilities, and the specialization of the teacher of the art science in his field of science, first of all, with the content and purpose of the history of the science. Modern views on the content and purpose of history are described with views on two opposite points of view, the social pedagogical necessity of developing human characteristics is highlighted through pedagogical influence
Keywords: history; personal virtue; professional culture